Integrating the use of endophyte-infected grasses (Barrier Festulolium) as a biological control method to combat aphids (Myzus persicae) and virus yellows in sugar beet - Shetty, Athreya Ratnakar (2025)
More than half of the UK sugar demand and 25% of the European sugar demand is met by indigenously grown sugar beet, making it one of the most economically important crops. The biggest threat to the sugar beet industry is virus yellows (VY) transmitted by peach potato aphids (Myzus persicae). The VY complex that consists of three different viruses, can cause yield losses ranging from 10 – 70% depending on the specificity and severity of the infection. Historically, neonicotinoids were used to control these viral vectors, however recent bans on these systemic pesticides owing to the harm they cause to beneficials has created a vacuum with no alternative available to combat the aphids and VY diseases (Francis et al., 2022). Thus, biological alternatives like endophyte-infected-infected grasses can play an important role in helping control pests and diseases. Barrier Festulolium is one such endophytic grass species developed by New Zealand based CropMark SeedsTM. Barrier associates with the symbiotic fungal species Epichloë uncinata. This fungus lives within the grass tissues and when under stress it releases lolines, a class of alkaloid based volatile compounds, that in turn has been proven to keep pests away in grassland systems. This project aimed to try and integrate these grasses into sugar beet cultivation in the UK with the hypothesis being that if the sugar beet can take up some of these lolines secreted by the grass, it may help confer deterrence to aphids, potentially reducing virus incidence. As part of the investigation, Barrier Festulolium as a seed meal at four different doses (25%, 50%, 100% and 200%) was trialled in a controlled environment along with a field trial looking three different seed rates of the grass (10, 20, 30 kg/ha and control) and four different cultivation strategies (strip treated, shallow till, deep till and glyphosate) in each of the seed rates. The controlled environment results showed that the seed meal applications did not prevent VY infection, but induced beneficial responses in crop, helping keep the beet canopies greener for longer. Additionally, they also had a biostimulant effect on the sugar beet with increases in canopy and root biomass in the higher doses. The results from the field trial showed similar results – while the endophytic grass did not prevent aphids and virus yellow infections, it did seem to affect disease as there were more individual plants with yellowed canopies rather than large patches. There were also significant differences in leaf chlorophyll content at higher grass seed rates, with the glyphosate and strip treated plots showing the greenest canopies. However, the shallow till treatments at 20 and 30 kg/ha proved detrimental to sugar beet, with lowest plant establishment, more stressed canopies with higher temperatures and lowest leaf chlorophyll, proving how crucial it is to ensure that the grass is destroyed at the right time to ensure minimal competition or phytotoxic effects on the beet. Overall, while the endophytic grass doesn’t prevent aphids/virus from affecting the beet, they are still a worthy biological alternative, as the beet show healthier canopies for longer and increased biomass accumulations, potentially translating to higher yields.